Jornalismo em processo: dinâmicas da cobertura socioambiental na imprensa brasileira - Pedrotti, Janaina Sarah (2017)
To think about journalism as a process, you have to look at the complex and diffuse paths of its practice to broaden the theoretical understanding of the scientific field. This thesis discusses the theme through the bias of the practice of commercial press with its organizational and structural characteristics and the singular relations. The corpus focuses on the entanglement of the journalistic practice around the press coverage in the socio-environmental area. The process of, production and edition is explored, considering also that these processes have impregnated the collective production dynamics, while it develops in apparent and contradictory individual activity. The adopted perspective is inserted in the discussion about the creation of communication networks processes in different entrances, in order to consider this entanglement of the process of creation in journalism, considering the procedural studies of Cecilia Salles. Texture that led to the expansion of the conception of the journalism making that this thesis brings, by looking at the coverage dynamics of the Folha de S. Paulo, Estado de S. Paulo, Folha do Estado (MT) newspapers and their respective websites with emphasis on the monitoring of the withdraw process in Marãiwetesédé in 2012 and 2013. And later in the journalistic coverage of the rupture of the tailings dam of the mining company Samarco in Bento Rodrigues, district of Mariana (MG) in 2015. The theoretical body is formed by a multidisciplinary framework of two interconnected central axes. The first is supported by a theoretical-methodological approach based on semiotics, subsidized in the formulations of C. Peirce, the complexus of E. Morin and the procedural perspective of C. A. Sales, which allowed us to understand nuances and questions that were not so comprehensible to other approaches. The second axis focuses on the discussions in the field of journalism under guardianship of theoretical such as M. Chaparro, R. Alsina and Medina in conceptual dialogues with the field. This background provided support for the meta-theoretical articulation around the connections in journalistic coverage brought by the dimensions: Expansion of journalistic making; shifts in journalistic coverage - from local to global; mobility of the team; sources of information and conflict and catastrophe in catharsis